A Serendipitous Synthesis: SiO2‐HNO3 Mediated Oxidative Aromatization and Regioselective Nitration of 1, 3, 5‐Trisubstituted‐4, 5‐Dihydro‐1H‐Pyrazoles. Issue 35 (17th September 2019) - Bhatia, Rimpy; Kadyan, Kulbir; Duhan, Meenakshi; Devi, Meena; Singh, Rahul; Kamboj, Ramesh C.; Kumar, Parvin
Abstract: Research often leads to unprecedented results that open the gates for new methodologies. We report herein the oxidative aromatization and serendipitous regioselective nitration of 1, 3, 5‐trisubstituted‐4, 5‐dihydro‐1 H ‐pyrazoles under mild reaction conditions using SiO2 ‐HNO3 as an oxidizing agent to afford 1, 3, 5‐trisubstituted pyrazoles with high regioselectivity. Here SiO2 ‐HNO3 acts as a nitrating agent along with oxidizing property. SiO2 ‐HNO3 is cheap, easy to prepare, eco‐friendly and practically applicable catalyst. Abstract : The oxidative aromatization and serendipitous regioselective nitration of 1, 3, 5‐trisubstituted‐4, 5‐dihydro‐1 H ‐pyrazoles under mild reaction conditions using SiO2 ‐HNO3 as an oxidizing agent to afford 1, 3, 5‐trisubstituted pyrazoles with high regioselectivity